Pemberdayaan Masyarakat Miskin Melalui Kelompok Usaha Bersama (KUBE) Di Kecamatan Bintan Timur Oleh Dinas Sosial Kabupaten Bintan - Muhammad Hidayat Nasmi; Karjuni Dt. Maani (Dialektika Publik, 2019)
Society empowerment are effort to increase society dignityin the current society. Because so many society can not be free from poverty and backwardness. Social agency of Bintan regency has empowered poor families for helping families in improving social welfare which society empowerment are one of many solution for resolve poverty problem. But in realty still found many problem. The purpose of this research was analyze society empowerment of poor through joint business ( Kube ) in sub-district of east bintan by Social agency of Bintan regency. the method used is descriptive with a qualitative approach and using primary and secondary data. Data collection techniques used in this study were interviews, observation, and documentation. The results of the study indicate that the program has not been able to improve the people who are members of the KUBE program. This was apparent in several joint business groups (KUBE) who had difficulties in marketing, because they were not given easy access to the management of halal labels and permits from BPOM. So that society have difficulty entering their products more broadly, because it is a requirement of supermarkets and mini markets and bazaars made by the private sector